Extracurricular activity : students performance in leadership and managerial competency in Students In Free Enterprise (SIFE) / Mohamad Zulfadli Mohd Amin - Mohd Amin, Mohamad Zulfadli (2011)
This study investigated the competency of the students who are involved with Students In Free Enterprise (SIFE) in leadership and managerial capacity. It also examined the relationship between students' involvement with extracurricular activities and students competencies and performance. The subjects of this study involved 82university students Universiti Teknologi MARA (UiTM), Universiti Tenaga Nasional (UNITEN), Universiti Malaysia Sabah (UMS), Universiti Malaysa (UM) and Universiti Teknologi Petronas (UTP) The study employed one system of collecting data, an online Questionnaire. The presentation of data is varied in the form of tables, charts and graphs. The findings in this study indicated students who involved in extracurricular activities have better management and leadership performance.